Inspiring a generation(?): Interconnecting discourses between governing actors, policy and legacy around London 2012 - Postlethwaite, V. (University of Worcester, 2020)
In this thesis, I critically examine governing actors, policy, and legacy discourses connected to the London 2012 Olympic and Paralympic Games` legacy aim to `inspire a generation.` In academic, political, and media scrutiny around the `inspire a generation` legacy aim the debates are frequently reduced to considering why policy changes or legacy initiatives have not resulted in observable increases in sport and physical activity among young people. I move beyond these debates to discuss the governing aspect and to contribute a perspective on how the legacy aim affected policy across the bidding, planning, delivery, and (ongoing) legacy of London 2012. I focus on how the official London 2012 educational programme (Get Set) affected discourses around domestic policy in the sport and education sectors. To achieve this, I employ a multimethod qualitative design (documentary evidence, political and policy dialogue, and semi-structured interviews) to, firstly, identify key policy and legacy documents related to the Get Set educational programme and the London 2012 `inspire a generation` legacy aim. Secondly, to explore discursive changes to legacy and policy from the perspective of a variety of governing actors that span across the state, commercial, and non-profit organisations. Given the importance placed on young people by the UK Government and the Olympic and Paralympic movements, the legacy aim intersects both domestic and international discourses, such as neoliberalism and ableism. The findings of the analysis are examined further through a theoretical lens influenced by the Foucauldian concept of governmentality. The findings and discussion demonstrate how policy and legacy discourses have been interpreted and utilised differently by governing actors, moreover, how such differences can be analysed through governmental ambitions, political rationalities, and governing technologies. The findings and discussion highlight, firstly, the ownership and responsibility of the `inspire a generation` legacy aim as there are distinct differences between the UK Government and the Olympic and Paralympic organisations formations of governing. Secondly, the intersection of legacy and policy around the visibility and legitimacy of the Paralympic movement and disabled young people. The thesis contributes to the ongoing debate around the London 2012 legacy. It suggests how the case of the `inspire a generation` legacy aim has implications for academics, policymakers, and other agents understanding of governing systems around young people, sport, and education.